Role Of Leadership Styles On Performance In An Organisation - Dev Kumar Kochiyel; Dr. Kumar Ashutosh (Revista Electronica de Veterinaria, 2024)
Enhancing an organization's success can be attributed in large part to leadership. The leadership in an organization determine its performance. This research paper explores various leadership theories and leadership styles and examines the relationship between several leadership styles with the organisational performance. A company's success is positively correlated with its leadership style because how well the business will perform depends on how the leader treats his/her employees. Productivity will rise as a result of a leader who engages employees and considers their opinions and suggestions when making choices. This is especially true when employees feel like they have a voice, which boosts motivation. When a leader wishes to implement the ideal leadership style inside an organisation, it all boils down to habit and mentalities. It has been concluded that leaders should strive to employ multiple strategies and tactics to meet organisational goals and augment its overall performance.